Effectiveness of Lomustine Combined With Bevacizumab in Glioblastoma: A Meta-Analysis - Ren, Xing; Ai, Di; Li, Tong; Xia, Lei; Sun, Lingzhi (Frontiers in Neurology, 2021)
Abstract Introduction Despite surgical and chemotherapeutical treatment options, the prognosis for glioblastoma (GBM) remains poor. Some studies have found that using lomustine plus bevacizumab to treat GBM can prolong overall survival (OS) and progression-free survival (PFS). The aim of this study was to explore the efficacy of the two drugs in combination treatment of GBM using a meta-analysis of the existing literature to help settle the ongoing debate. Materials and methods PubMed, EMBASE, and Cochrane Library were searched for the effectiveness of lomustine plus bevacizumab in GBM literature updated in June 6, 2020. The main outcomes we analyzed were PFS and OS; we also analyzed the effects of this drug combination on 6-month PFS which represents the percentage of patients who had PFS for six months. All the data were pooled: OS and PFS with the mean difference (MD) and 6-month PFS with the risk ratio (RR). Because there were different control groups and dose groups, we ran two subgroup analyses to make sure they were comparable. All statistical analyses were performed using the Review Manager Version 5.3 software. Results Six clinical trials were identified which included 1095 patients (treatment group: 516; control group: 579). The group treated with lomustine and bevacizumab showed improvement in OS (MD =1.37; 95% CI, 0.49–2.25; p=0.002)，PFS (MD =0.23; 95% CI, 0.13–0.34; p<0.00001) and 6-month PFS (RR =2.29; 95% CI,1.43-3.65; p=0.0005). Two subgroup analyses of the main outcome, OS, show that the results of Control group A (p=0.01) and Dose group 2 (p=0.003) are significantly different from those of the other control groups or dose groups. Conclusion This study shows that lomustine and bevacizumab can effectively increase OS, PFS and 6-month PFS in patients with GBM. The encouraging results of lomustine and bevacizumab combination therapy for GBM should be studied in more clinical trials in the future.